Dietary Fibres: Their Analysis in Animal Feeding, and Their Role in Rabbit Nutrition and Health - Gidenne, Thierry (Indonesian Bulletin of Animal and Veterinary Sciences, 2013)
Two centuries ago Heinrich Einhof developed the so-called Weende method (crude fibre), to first deals with the fibre content of the feeds for ruminants, and proposes to isolate a residue called the "crude fibre". Then, dietary fibre concepts evolve and differ in animal feeding compared to human nutrition and health. Animal nutritionists deal with various fibre sources, often from whole plants (forages, by products of seeds processing), and recover a larger range of polysaccharidic components, including other polymers, such polyphenolic (lignins, tannins) or polylipidic compounds (cutins). Dietary fibres are generally defined as polysaccharides and associated substances resistant to mammal enzyme digestion and absorption that can be partially or totally fermented in the gut. However, today this topic is still subjected to very active research, because of the complexity of the physical structure and chemical composition of the plant cell walls, and in the wide and different physiological effects of these different constituents. The importance of dietary fibre in animal feeding is due to its influence on rate of passage, mucosa functionality and its role as substrate for gut microbes performances and digestive health. This review will describe the definition and different structure of fibres and cell wall constituents and their analytical methods. Â  Key words: Dietary fibre, analysis, rabbit, nutrition, health